2021
DOI: 10.13107/jocr.2021.v11.i05.2210
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Femoral Neck Fractures after Sliding in a Water Slide: A Case Report of Two Patients

Abstract: Introduction: In contrast to adults, fractures of the neck of femur in children are relatively rare. The commonly described mechanism of injury is high energy trauma. Treatment options are almost always surgical. Prognosis, which entails relatively high rates of complications, varies with specific anatomic location, time to surgery, and reduction quality. Case Report: We describe two cases of 10- and 12-year-old girls who suffered a fracture of the neck of the femur, Delbet Type II and Type III, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Rinat et al [16] reported two cases who suffered from femoral neck fracture which classified as Delbet type II and III, in 2021. The younger one showed signs of AVN in 1 year of follow-up while the other one had a good outcome without any sign of AVN after 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Rinat et al [16] reported two cases who suffered from femoral neck fracture which classified as Delbet type II and III, in 2021. The younger one showed signs of AVN in 1 year of follow-up while the other one had a good outcome without any sign of AVN after 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%